The British Parliamentary Debate Practices in Promoting English Speaking Proficiency: A Systematic Literature Review in Multiple EFL Cases - Waluyo, Gatot Hadi; Abrar, Mukhlash (PPSDP International Journal of Education, 2024)
This systematic review of the literature explored the impact of The British Parliamentary Debate Practice from several studies. The present study focused on the way debate practice enhances students’ English-speaking abilities in an EFL context. The PRISMA method stages to search journal databases was used in this study. However, after an intensive selection process, the researcher found that 11 articles from 3 reputable databases such as Google Scholar, Scopus, and Semantic Scholar had the most relevant and suitable content to answer the purpose of this Systematic Review study. The research findings revealed that the implementation of British Parliamentary Debate in English language teaching is highly effective to improve speaking skill. Besides, through this learning method, several aspects such as; linguistic skill, vocabulary, self-confidence, and self-awareness of students at various levels of education can also be increased. The researcher also found that there are learning stages using British Parliamentary Debate that can be adapted by teachers to improve the teaching of students’ speaking skills such as AREL (Argument, Reasoning, Evidence, Link Back) technique. In addition, the current study includes a number of recommendations.